Female athlete sport science versus applied practice: bridging the gap - Burden, R. J., Biswas, A., Hackney, A. C. (International Journal of Sports Physiology and Performance, 2024)
Background: Female-specific science, medicine, and innovation have grown steadily since the turn of the decade as the focus on female sport continues to advance. While this growth is welcome, and despite the best of intentions, it is not always coupled with valuable application.